Prognostic significance of infectious episodes occurring during first‐line therapy for diffuse large B‐cell lymphoma ‐ A nationwide cohort study. Issue 3 (28th May 2020) - Clausen, Michael R.; Ulrichsen, Sinna P.; Juul, Maja B.; Poulsen, Christian B.; Iversen, Brian; Pedersen, Per T.; Madsen, Jakob; Pedersen, Robert S.; Josefsson, Pär L.; Gørløv, Jette S.; Nørgaard, Mette; d'Amore, Francesco
Abstract: Infections during first‐line therapy for DLBCL are often associated with chemotherapy dose reductions and increased mortality. Systemic infections have also been suggested as beneficial promotors of immunological responses. However, whether there is an association between the timing of an infectious episode and outcome during treatment has not yet been clarified. We investigated how the occurrence and timing of infectious episodes during the first line of treatment for "de novo" DLBCL influenced patient outcome. We used data on DLBCL patients from the Danish Lymphoma Registry, the Danish National Patient Registry, and the Danish National Pathology Registry. Infections were categorized according to type (ICD‐10) and time of occurrence after treatment start. "Early" infections were defined as occurring between days 7 and 42 and "late" infections between days 100 and 150 from treatment start. Patients experiencing both "early and late" infections were categorized separately. We used multivariable Cox regression and Kaplan‐Meier estimates to assess the association between infections and survival adjusting for NCCN‐IPI, sex, comorbidity, and rituximab treatment. We identified 3546 patients, median age 65 years (IQR 56, 73). Infectious episodes occurred in 1171 (33%) patients, of which 666 had "early, " 303 "late, " and 202 both "early and late" events. Patients without registered infections had a 5‐year overall survival (OS) rates of 74%. Those with "early, " "late, " or "early+late" had 5‐year OS of 65%, 62%, and 53%, respectively. Compared with patients without any registered infections, hazard rate ratios (HR) were 1.24 (95% CI 1.05‐1.47), 1.32 (95% CI 1.06–1.63), and 1.59 (95% CI 1.27‐2.00), respectively, in the multivariable model. We observed that infectious episodes during first‐line treatment for "de novo" DLBCL occurred in 44% of the patients. Irrespective of timing, patients with infectious episodes had an inferior outcome compared to those without. Outcome patterns were similar for patients registered with sepsis.